The Effectiveness of Acceptance and Commitment Therapy on Marital Frustration and Attitude Towards Divorce Among Married Women on the Verge of Divorce - Rahimi, Bahare; Salarkarimi, Najmeh; Rastegar Kuchaksaraei, Morvarid; Taherkhani, Mina; Mohammadali Nasab, Shamim (Psychology of Woman Journal, 2023)
Objective: The current research aimed to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on marital frustration and attitudes towards divorce among married women on the verge of divorce. Methods and Materials: This study utilized a quasi-experimental design with a pre-test and post-test control group. The population consisted of married women on the verge of divorce visiting counseling centers in Tehran in 2022. The sample, selected via convenience sampling, included 28 individuals divided into an experimental group and a control group (14 participants each). Data were collected using questionnaires on marital frustration and attitudes toward divorce. The experimental group received ACT-based treatment for eight weeks, with one 90-minute session per week, while the control group did not receive any specific intervention. Findings: Findings indicated significant differences between the experimental and control groups in scores of marital frustration and attitudes toward divorce in the post-test compared to the pre-test. Conclusion: Therefore, Acceptance and Commitment Therapy significantly affects marital frustration and attitudes towards divorce among married women on the verge of divorce.